“Knowledge Economy” as a Resource for the Intensification of Socio-Economic Transformation of the Regional Economic Space - Shiryaev, Dmitry V.; Artemova, Elena I.; Zelinskaya, Maria V.; Novoselov, Sergey N.; Galiullina, Svetlana D.; Pismennaya, Elena E. (International Review of Management and Marketing, 2016)
In 2000, at the Lisbon summit of the Council of Europe has formulated a strategic goal of the EU in the coming century - to become by 2010 “the most competitive and dynamic economy in the world based on knowledge, capable of sustainable economic growth, along with an increase in the number and quality of jobs and strengthening social cohesion”. European Commission report notes that the core of the economy based on knowledge and the knowledge society is the combination of four elements: 1) the production of knowledge; 2) the transfer of knowledge through education; 3) the dissemination of knowledge through information and communication technologies; 4) The use of knowledge in technological innovation. We mean “knowledge economy” - as an economy in which knowledge and innovation play a dominant role in economic development. The emergence of the knowledge economy is characterized by the increasing role of knowledge as a factor of production and their significant impact on the qualifications, training, organization and innovation. Keywords: knowledge-based economy, regional economics, economics of education JEL Classifications: A2; D8; P25